2021
DOI: 10.4236/ojpsych.2021.111005
|View full text |Cite
|
Sign up to set email alerts
|

The <i>Hikikomori</i> Phenomenon: Could Loneliness Be a Choice of Self-Restriction from Society?

Abstract: Originated in Japan, the hikikomori phenomenon-as a form of individual withdrawal-has progressively widespread and gained international attention, given its psycho-social and economic consequences. In fact, hikikomori appears today as a problem that cannot be confined solely to the field of mental health. Rather, it appears as a phenomenon that concerns many aspects of modern society, intersecting with medicine, sociology, anthropology, politics, economics, culture and education. In the context of the actual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Zauważa się jednak dynamiczny rozwój gier oraz narzędzi komunikacji dostępnych poprzez komputery i telefony, w których pokłada się duże nadzieje na poprawę sytuacji części hikikomori. Wskazuje się jednak, iż wiele osób hikikomori może preferować metody leczenia oparte na kontakcie bezpośrednim z innym człowiekiem (Castelpietra, Nicotra, Leo, 2021). Oprócz działań social contact to online only and online medical appointments.…”
Section: Technologie Jako Narzędzie Terapiiunclassified
“…Zauważa się jednak dynamiczny rozwój gier oraz narzędzi komunikacji dostępnych poprzez komputery i telefony, w których pokłada się duże nadzieje na poprawę sytuacji części hikikomori. Wskazuje się jednak, iż wiele osób hikikomori może preferować metody leczenia oparte na kontakcie bezpośrednim z innym człowiekiem (Castelpietra, Nicotra, Leo, 2021). Oprócz działań social contact to online only and online medical appointments.…”
Section: Technologie Jako Narzędzie Terapiiunclassified
“…Moreover, boredom proneness may also act as a predictor of the overdependence on a certain object (and, hence, technology) [32]. Loneliness may favor the likelihood in developing depressive and anxiety disorders, alcohol and/or substance use and abuse, as well as incentivizing smoking habits [39]. Both these dimensions have been further investigated due to their dramatic increase among young people, particularly during the COVID-19 pandemic [38,[40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…1 A survey done by the Japanese Cabinet Office in 2019 found that the number of hikikomori individuals between the ages of 15 and 65 years reached 1.15 million. 2 A gender difference of 3:1 ratio, with more male hikikomori (63.3%) than female cases (36.7%), have been observed. There is a bimodal distribution of age among hikikomori individuals, which peaks at the age of 20 and 50.…”
mentioning
confidence: 96%
“…1 According to the guideline by the Japanese Ministry of Health, Labor, and Welfare on hikikomori, the characteristics of hikikomori include no intention to work or study with a lifestyle concentrated around the home for more than 6 months, limited social relationships, with no other mental disorders. 2 In 2019, Kato et al established a diagnostic system, highlighting significant impairment in function and distress associated with social withdrawal. The list included specifiers (lack of social participation, lack of face-to-face social interaction, indirect communication and loneliness) that help to characterize hikikomori.…”
mentioning
confidence: 99%
See 1 more Smart Citation